Dynamic maintenance of data distribution for selectivity estimation - Whang, Kyu-Young; Kim, Sang Wook; Wiederhold, Gio (1991)
Abstract: "We propose a new dynamic method for multidimensional selectivity estimation for range queries that works accurately independent of data distribution. Good estimation of selectivity is important for query optimization and physical database design. Our method employs the Multilevel Grid File (MLGF) for accurate estimation of multidimensional data distribution. The MLGF is a dynamic hierarchical balanced multidimensional file structure that gracefully adapts to nonuniform and correlated distributions. We show that the MLGF directory naturally represents a multidimensional data distribution. We then extend it for further refinement and present the selectivity estimation method based on the MLGF
Keywords: Database design; Database management